FISH ACUTE TOXICITY TESTING OF LITSEA GARCIAE METHANOLIC EXTRACT IN ADULT ZEBRAFISH - SITI ZALEHA, RADUAN; Muhammad Hamdi, Mahmood; Ahmed, Qu; Shaikh, MF; Rusmili, MRA; Wan Sulaiman, WMA; Hamdi, M. M.; Kasmuri, AR (2021)
Litsea garciae bark (LG) is currently used in Sarawak by locals to treat various diseases traditionally. However, there is no preliminary study conducted to evaluate the respective plant's acute toxicity up to the present time. The recent study's main objective was to determine the LG bark methanolic extract's acute toxicity in adult zebrafish.The research was approved by IIUM Animal Care and Use Committee (I-ACUC) from IIUM, IIUM/IACUC-2019(21). The raw LG bark underwent a successive maceration technique and freeze-dried. The methanolic extract was administered in a static system by immersion based on OECD Test Guideline No 203. The acute toxicity test implemented 96 hours of observation for any mortality or visible abnormalities related to the zebrafish's appearance and behaviors. As the results, the test group (limit 100mg/L) and the control group recorded zero mortality and no significant abnormalities. Hence, LC50 was not determined. In agreement, the present findings revealed the significance of relatively safe and less toxic methanolic extract of LG bark for further biomedical applications.